A New Playing Method of the Guessing Football Lottery. Issue 1 (March 2020) - Liu, Shunqi; Wang, Yuxin; He, Hong
Abstract: This paper analyzes the impact of sports lottery buyers' opinions on the prediction of sports lottery and betting behavior, and designs a new "sky ladder" strategy. This strategy improves the existing playing methods in both amusement and flexibility. The author discusses the feasibility of the new strategy and its final influence over lottery companies and lottery buyers, simulates and predicts the effects of the brand-new strategy based on BP and LSTM neural network algorithms, and works out a series of simulation results that show the risks of the new playing method are well controlled.